SEASONAL VARIATION IN HEMOGLOBIN CONCENTRATION AND HEMATOCRIT VALUE - NERIISHI, SHOTARO; SAGAN, LEONARD A.; FUKUSHIMA, KAZUKO (Japanese Journal of Tropical Medicine and Hygiene, 1973)
The observation that hemoglobin concentration and hematocrit value vary with the season has not been generally accepted but studies made in Japan support this. Reported here are the results of analysis on the month-specific mean hemoglobin concentration and hematocrit values from 29, 482 blood samples collected during the 5 years from 1958 to 1963 from ABCC JNIH Adult Health Study sample members in Hiroshima and Nagasaki. The values show definitely that seasonal variation is present. Both hemoglobin and hematocrit values showed a pronounced negative correlation to temperature and humidity. It was found on grouping the subjects by sex, age, and relative weight that the range of seasonal variation was greater in older persons than in younger, and in obese persons than in those of light weight. It was characteristic that the range of seasonal variation was small in the groups with high levels and, contrarily, large in the group with low levels. The two extremes were presented in males under 40 years of age of the light relative weight group, and in obese males aged 40 and over.